O enfrentamento da covid-19 e a saúde mental dos auxiliares e técnicos de enfermagem de um hospital público da grande Vitória, ES - Silva, Juliana Oliveira (2022)
The precariousness of the SUS has intensified in recent years with neoliberal politics and produced effects on care practices and in the mental health of health workers. These issues became even more evident with the emergence of the Covid-19 pandemic in March 2020, which overwhelmed health services. From the work experience in a public hospital in Grande Vitória/ES, the proposal of this research emerged, which aims to analyze the relationship between work and mental health of nursing assistants and technicians in the context of the Covid-19 pandemic. A lot of information supported the study and the data was produced through different strategies, among them, conducting conversation circles with hospital workers and semi-structured interviews with eight nursing assistants and technicians who worked directly with Covid-19 patients hospitalized in a medical clinic unit. Some concepts of Psychodynamics of Work guided the discussion of data that were evaluated based on the technique of Nucleus of Senses Analysis (Análise de Núcleos de Sentido). In addition to the rigid division of work, the invisibility of know-how, the overload of work, the weakening of the collective and the recognition of work and the absence of spaces for collective discussion, nursing assistants and technicians began to deal with other factors of suffering during the pandemic, namely: insecurity and fear of being infected by the new coronavirus or being responsible for the infection of a family member, insecurity in performing unknown activities and the intensification of work. Despite the harmful context for mental health, these workers find a space for creation and report pleasure and satisfaction at work when they perceive their contribution to the improvement and discharge of the patient, besides presenting some strategies that seem to have contributed to handle the suffering. The study also showed that the changes in the conditions and organization of work made possible by the flexibility of budget limits because of the declaration of the State of Public Calamity and the State of Public Emergency in the period of the Covid-19 pandemic associated with the strategies of hospital managers have improved the work context of nursing assistants and technicians in the medical clinic even if of the demands and challenges imposed by the pandemic are many, which allows us to infer the harmfulness of neoliberal policies for health work.